LA FRONTERA CHACO-SALTEÑA DESDE UNA PERSPECTIVA GEOGRÁFICA Y ANTROPOLÓGICA: LA IDENTIDAD EN UN ÁREA DE CONTACTO INTERPROVINCIAL - Ariel Bonfanti, Fernando (2005)
The present research paper’s objective is to identify the problematic within the spaces labelled as Frontiers, specifically the Chaco-salteña frontier, aiming to know its cultural and socio-economic traits. We set off considering that a distinctive trait of frontier areas is to imagine them as complex spaces where the interaction of distinctive peoples takes place, altogether with its cultural, economic and social traits, whose activities are transferred. And where daily sharing is not translated necessarily to the local population in a shared self-awareness or “frontier identity”, but the dynamics of daily interaction can arise conflict between groups.